ENVIRONMENTAL REGULATION OF POLLUTANTS OF ENTERPRISES FOR EXTRACTION AND PROCESSING OF NON-METALLIC ROCKS (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The article contains environmental regulation of emissions and discharges of pollutants on the environment by establishing standards for maximum allowable concentration (MAC) and maximum allowable discharges (MAD). Also, the generation and disposal of production and consumption waste by establishing standards for maximum allowable waste (MAW). Environmental regulation of pollutants of non-metallic rock mining and processing enterprises is considered. The procedure for the implementation of environmental regulatory projects and the calculation methods for determining pollutants, specific indicators, generation standards and waste disposal limits are presented. The results of the study are data from the project of MAC standards of the Djam’s field for the production and processing of marble developed according to the proposed method of implementation and calculation.